Targeted interventions for children with arithmetical difficulties - Dowker, A (British Psychological Society, 2010)
Background. Difficulty with arithmetic is a common problem. There is increasing evidence that arithmetical cognition is made up of multiple components, and that it is quite possible for children and adults to show strong discrepancies, in either direction, between the components. This suggested the desirability of developing interventions that assess and target children’s weaknesses in specific components of numeracy. Aims. This paper reports two related studies of targeted interventions for children with mathematical difficulties. The aim was to develop intervention techniques, based on assessing and targeting specific strengths and weaknesses, and to assess their effectiveness. Sample. The first study, of the pilot Numeracy Recovery intervention programme, included 169 children aged 6 and 7,. The second study, of the Catch Up Numeracy programme, included 246 children between the ages of 6 and 10, of whom 154 received the Catch Up intervention program. 50 were given the same amount of time for non-targeted individualized mathematics work, and 42 children received no intervention, except for the usual school instruction Both samples consisted of children, who had been identified by their teachers as having difficulties with arithmetic. Method. The first study took place in Oxford, and children were assessed on nine components of early numeracy. The project has since been adapted , under the name of Catch Up Numeracy, for wider use, and tested in 11 local authorities in the United Kingdom. The second study, which included ten components of numeracy, involved teachers and teaching assistants receiving formal training from the Catch Up organization in delivering the programme. In both studies, following assessment, the children received weekly intervention (half an hour a week for approximately 30 weeks) in the components with which they had difficulty. The children were given standardized tests at the beginning and end of intervention. In the first study, the tests used were the Basic Number Skills subtest of the British Abilities Scales; the Numerical Operations subtest of the Wechsler Objective Numerical Dimensions; and the Arithmetic subtest of the WISC. In the second study, the test used was the Basic Number Screening Test. Results. The children in the first study showed significant improvement, relative to their age group, on the three standardized tests. In the second study, the children in the Catch Up intervention program made more than twice as much progress in ‘mathematics age’ as would have been expected by the passage of time. Their progress was significantly greater than that of either of the control groups. Conclusions. The findings support the view that individualized interventions in arithmetic, especially those that focus on the particular components with which an individual child has difficulty, can be highly effective. Moreover, the amount of time given to such individualized work does not, in many cases, need to be very large to be effective. Thus, children's arithmetical difficulties are highly susceptible to intervention.